Persistent organic pollutants (PAH, PCB, TPH) in freshwater, urban tributary and estuarine surface sediments of the River Clyde, Scotland, UK. (13th November 2018) - Vane, Christopher H.; Lopes dos Santos, Raquel A.; Kim, Alexander W.; Moss-Hayes, Vicky; Fordyce, Fiona M.; Bearcock, Jenny M.
ABSTRACT: Surface sediments from a 160-km stretch of the River Clyde, Scotland, were analysed for persistent organic pollutants to investigate distribution, source and environmental effect. Glasgow's urban tributaries polyaromatic hydrocarbons (PAH) ranged from 2.3 to 4226mgkg –1, total petroleum hydrocarbons (TPH) 72 to 37879mgkg –1 and polychlorinated biphenyls (PCB) 3 to 809μgkg –1, which were more polluted than the upper River Clyde PAH that ranged from 0.1 to 42mgkg –1, TPH 3 to 260mgkg –1 and PCB 2 to 147μgkg –1 . Intermediate values of the inner Clyde estuary PAH ranging from 0.6 to 30mgkg –1, and PCB ranging from 5 to 130μgkg –1, were attributed to point sources and sediment transfer from the urban tributaries. Comparison with sediment quality criteria suggested possible adverse effects on aquatic biota. PAH isomeric ratios confirmed a pyrolytic source throughout the Clyde and benzo[ a ]pyrene/benzo[ g, h, i ]perylene ratios >0.6 confirmed that upper, urban and estuarine domains all to a lesser or greater extent accumulated PAH from traffic emissions. The degree of chlorination determined from PCB homologues differed in each of the three domains, suggesting variable source or that the process aerobic/anaerobic degradation varied in each of the three domains. The anthropogenic impact of the city of Glasgow can be quantified in that the urban tributary sediment mean values were 60 (PAH), 33 (TPH) and 11 (PCB) times higher than the rural upper Clyde counterpart.